Self-regulating reversible photocatalytic-driven chromism of a cavity enhanced optical field TiO2/CuO nanocomposite. Issue 22 (24th May 2017) - Gao, Minmin; Ng, Serene Wen Ling; Chen, Lianwei; Hong, Minghui; Ho, Ghim Wei
Abstract : We demonstrate a cavity enhanced optical field nanocomposite with self-regulating reversible photocatalytic-driven chromism for transmittance modulation and high-resolution ink-free rewritable patterning/printing. Abstract : Over the years, the exploration of inorganic chromogenic materials commonly interfaced with expensive noble metals has been limited, while the study of organic photochromic materials has proliferated. The key challenge lies in the optimization of inorganic materials' constituents and structural design to achieve enhanced light–matter interaction chromism with performance commensurate with that of their organic counterparts. Here, we demonstrate a tailored inorganic transition metal cavity that boosts optically controlled reversible and repeatable chromism driven by a photocatalytic reaction. The solution-processable TiO2 /CuO nanocomposite is endowed with a mesoporous cavity that is highly adept at performing self-regulating reversible photochromism under solar irradiation. The improved photoreactive chromism stems from the tailored critical structural parameters of the highly accessible mesoporous shell, reduced charge carrier diffusion length thin shell, and cavity enhanced optical field for photon–matter interactions. Consequently, the nanocomposite exhibits dual-functional photoregulated effects, i.e. photochromism mediated light transmittance modulation and rewritable printing/patterning. The nanocomposite offers high sensitivity, resulting in a short response time due to the efficient charge transfer, and such chromism effects are stable in the ambient environment. Furthermore, controlled switching of the chromism effects may be obtained simply by low-temperature heating. The concerted combination of inexpensive materials/production, low toxicity and a highly transparent noble metal-free inorganic nanocomposite renders chromogenic properties that will trigger a renewed interest in smart light-stimulus integrated technology.